FAKTOR FAKTOR YANG BERHUBUNGAN DENGAN MOTIVASI MAHASISWA FAKULTAS KEPERAWATAN UNIVERSITAS RIAU DALAM MELAKUKAN DONOR DARAH - Aditya Nugraha; Gamya Tri Utami; Rismadefi Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Blood donation is the activity of donating blood that will be stored in the blood bank or blood transfusion needs. Factors that encourage individuals to commit blood donors one of them is motivation. The motivation of a person's blood donation is influenced by several factors, namely knowledge, social environment, altruism, and experience. This aim of this research was to know the factors that related to student’s motivation in blood donation. The design of this research was a descriptive correlation with a cross sectional method. The sample of this study was 77 students as respondents, taken using accidental sampling techniques. The measurement instruments used were questionnaire sheets for knowledge variables, social environment variables, altruism variables, experience variables, and motivation variables. The data analysis used was the chi square test. The results showed that of the 4 factors studied there were two factors which concluded that there was a relationship with the motivation of students in blood donation, namely the factor of knowledge with motivation, obtained p value of 0.044 < α (0.05) and social environmental factors with motivation obtained p value of 0.015 < α (0.05). Two other variables concluded that there was no relationship with student motivation in conducting blood donations, namely altruism with the results of p value 0.721 > α (0.05) and experience with the results of p value 0.942 > α (0.05). Based on the results of the research obtained, it is recommended that the blood donation unit of the City of Pekanbaru to further increase the interest of the community by providied counseling about the benefits of blood donation.Keywords: Blood donation, college student, motivation